Revisiting the Role of Islamic Boarding Schools in Shaping Digital Citizenship Among Gen Z Students - Aah Khoriah; Saona Saona (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2025)
Development rapid digital technology bring impact significant to pattern interaction , learning , and identity social generation Z. In context this , role institution Islamic education , in particular Islamic boarding school , become the more strategic in form character and digital ethics of Islamic boarding school students . Islamic boarding schools , as institution that combines spiritual, moral and social values , have potential big in internalize principles of digital citizenship based on mark Islam . However , the relevance and readiness Islamic boarding school in guide generation Z faces challenges of the digital era need reviewed in a way in- depth research This aiming For to study return role Islamic boarding school in forming digital citizenship among people student generation Z, as well as identify practice best , challenges , and coaching strategies that have been conducted . Research This use approach qualitative with method studies cases in some Islamic boarding school based technology in Indonesia. Data collection techniques include interview in-depth , observation participatory , and study document . Research results show that part Islamic boarding school has start integrate digital literacy , ethics media social , and responsibility digital answer in non-formal curriculum and activities extracurricular . However , there are variation in approach , depending on the vision leadership Islamic boarding school , access technology , and capacity source Power human . Research This recommend strengthening digital capacity of educators Islamic boarding school as well as integration values maqashid sharia in digital citizenship education